y = 2x – 1 y=-3x + 4 Solve the following system of equations for x

Question

y = 2x – 1
y=-3x + 4
Solve the following system of equations for x

in progress 0
Linh Đan 5 months 2021-08-26T11:55:31+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-08-26T11:56:47+00:00

    Answer:

    x = 1

    General Formulas and Concepts:

    Pre-Algebra

    Order of Operations: BPEMDAS

    1. Brackets
    2. Parenthesis
    3. Exponents
    4. Multiplication
    5. Division
    6. Addition
    7. Subtraction
    • Left to Right

    Equality Properties

    • Multiplication Property of Equality
    • Division Property of Equality
    • Addition Property of Equality
    • Subtract Property of Equality

    Algebra I

    • Solving systems of equations using substitution/elimination

    Step-by-step explanation:

    Step 1: Define Systems

    y = 2x – 1

    y = -3x + 4

    Step 2: Solve for x

    Substitution

    1. Substitute in y:                   2x – 1 = -3x + 4
    2. Add 3x on both sides:       5x – 1 = 4
    3. Add 1 to both sides:           5x = 5
    4. Divide 5 on both sides:     x = 1
    0
    2021-08-26T11:56:54+00:00

    Answer:

    y = 2x - 1 \: and \: y =  - 3x + 4 \\replacing \: the \: value \: of \: y, \: we \: get  \\ 2x - 1 =  - 3x + 4 \\ 5x = 5 \\  \boxed{x = 1}

    x= 1 is the right answer.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )